Hypoxia and HIF-1 increase S100A8 and S100A9 expression in prostate cancer - Grebhardt, Sina; Ströbel, Philipp; Mayer, Doris (International journal of cancer, 2012)
S100A8 and S100A9, two heterodimer-forming members of the cytosolic S100 Ca(2+) signaling protein family, are overexpressed in various cancer types, including prostate cancer. They act as proinflammatory danger signals when secreted to the extracellular space and are thought to play an important role during tumorigenesis, affecting inflammatory processes, proliferation, invasion and metastasis of tumor cells. Despite this fact, little is known about tumor environmental factors influencing S100A8/A9 expression. The aim of this study was to test the effect of hypoxia and its master transcriptional regulator hypoxia-inducible factor 1 (HIF-1) on S100A8/A9 expression. Hypoxia treatment resulted in induction of S100A8/A9 protein and mRNA expression in prostate epithelial BPH-1 cells, the latter was also confirmed in the prostate cancer cell lines PC-3 and DU-145. Furthermore, overexpression of HIF-1α caused increase in S100A8/A9 protein and mRNA expression as well as secretion. Functional hypoxia response elements mediating promoter activation on HIF-1α overexpression were identified within the S100A8 and S100A9 promoters using promoter luciferase reporter constructs. Binding of HIF-1α to S100A8 and S100A9 promoters was confirmed by chromatin immunoprecipitation. Immunohistochemical analysis of a prostate cancer tissue array showed clear correlation of S100A8 and S100A9 with HIF-1α expression. Multivariate proportional hazard analysis revealed association of high S100A9 level with time to prostate cancer recurrence. In conclusion, we identified hypoxia and HIF-1 as novel regulators of S100A8/A9 expression in prostate cancer. S100A9 might be useful as prognostic marker for prostate cancer recurrence after radical prostatectomy.